Seasonal variations of enteric peritonitis in Belgium and France : RDPLF data - Pacha Bakhtar; Evelyne Maillart; Frederic Collart; Christian verger (RDPLF, 2022)
Summary Little information is available on the seasonal ecology of germs responsible for peritoneal dialysis peritonitis. We performed a retrospective study based on RDPLF data covering the last 20 years and 20411 episodes of peritonitis. We show that the percentage of enteric peritonitis is highest in summer, lowest in winter and identical in spring and autumn. This higher proportion of organisms of enteric origin in summer has itself tended to increase in recent years. We postulate that a food contamination by enteric germs associated with an increased bacterial translocation at the level of the digestive tract itself favoured by constipation, as well as changes of the food nature could be responsible for this phenomenon. These seasonal variations may suggest that probabilistic initial antibiotic therapy should be adapted in cases of suspected peritonitis before the results of bacteriological analysis.